<u>Answer-</u>
<em>Cooper will receive </em><em>$12.00</em><em> at the end of the month.</em>
<u>Solution-</u>
Cooper has $1500 in the account now and he deposits an additional $500 at the beginning of the month.
So the total principal becomes 1500+500 = $2000
Given here,
APR = annual percentage rate = 7.2%
But as we have to calculate the monthly interest, so monthly interest rate would be ![=\dfrac{7.2}{12}=0.6\%](https://tex.z-dn.net/?f=%3D%5Cdfrac%7B7.2%7D%7B12%7D%3D0.6%5C%25)
Time period = 1 month
So, the interest after 1 month will be,
![\text{interest}=\dfrac{\text{Principal}\times \text{Rate of interest}\times \text{Time period}}{100}](https://tex.z-dn.net/?f=%5Ctext%7Binterest%7D%3D%5Cdfrac%7B%5Ctext%7BPrincipal%7D%5Ctimes%20%5Ctext%7BRate%20of%20interest%7D%5Ctimes%20%5Ctext%7BTime%20period%7D%7D%7B100%7D)
![=\dfrac{2000\times 0.6\times 1}{100}](https://tex.z-dn.net/?f=%3D%5Cdfrac%7B2000%5Ctimes%200.6%5Ctimes%201%7D%7B100%7D)
![=\$12.00](https://tex.z-dn.net/?f=%3D%5C%2412.00)
Therefore, Cooper will receive $12.00 at the end of the month.
Answer:
To a power, elevated to something
Answer:
4x^3 +10x
Step-by-step explanation:
for f(x) × g(x) you should multiply their functions :
(2x^2+5)×(2x) = 4x^3 +10x
This one is so easy that your brain refuses to accept it.
It's looking for a harder answer, but can't find it !
You're totally correct, as far you went. x² + 2x does = -1
Now add ' 1 ' to each side: x² + 2x + 1 = 0
Can you factor that quadratic ?
Can you mash it through the quadratic formula ?
Actually, it's the simplest possible perfect square.
x² + 2x + 1 = (x + 1)²
So the solutions of x² + 2x + 1 = 0 are both x = -1 .
Don't say anything.
I know it's embarrassing.
Answer:
![x - y = 0](https://tex.z-dn.net/?f=x%20-%20y%20%3D%200)
Step-by-step explanation:
Required
The graph equation
From the graph, we have:
![(x_1,y_1) = (0,0)](https://tex.z-dn.net/?f=%28x_1%2Cy_1%29%20%3D%20%280%2C0%29)
![(x_2,y_2) = (1,1)](https://tex.z-dn.net/?f=%28x_2%2Cy_2%29%20%3D%20%281%2C1%29)
The slope of the graph is:
![m = \frac{y_2 - y_1}{x_2 - x_1}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7By_2%20-%20y_1%7D%7Bx_2%20-%20x_1%7D)
![m = \frac{1-0}{1-0}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7B1-0%7D%7B1-0%7D)
![m = \frac{1}{1}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7B1%7D%7B1%7D)
![m =1](https://tex.z-dn.net/?f=m%20%3D1)
So, the graph equation is:
![y = m(x - x_1) + y_1](https://tex.z-dn.net/?f=y%20%3D%20m%28x%20-%20x_1%29%20%2B%20y_1)
![y = 1 * (x - 0) + 0](https://tex.z-dn.net/?f=y%20%3D%201%20%2A%20%28x%20-%200%29%20%2B%200)
![y = 1 * x](https://tex.z-dn.net/?f=y%20%3D%201%20%2A%20x)
![y = x](https://tex.z-dn.net/?f=y%20%3D%20x)
In standard form, we have:
![x - y = 0](https://tex.z-dn.net/?f=x%20-%20y%20%3D%200)